The Effectiveness of Spontaneous Group Discussion in Skills Speaking in Junior High School Students - Putri Adinda Yudha (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2023)
This research was conducted with the aim of finding out the effectiveness of the implementation of a cooperative learning model by utilizing the Spontaneous Group Discussion method on the speaking skills of grade VIII students at SMP Muhammadiyah 1 Jember. Experimental research through One Group Pretest-Posttest Design research design was applied as the type of research. In this research, the samples used were students of class VIII B with a total of 18 students. Tests were applied as a data collection technique in this research, where the results of the tests were analyzed by statistics, namely finding values by utilizing formulas. Based on the acquisition of data findings in the field, the pretest result was 55 and the posttest result was 82. The results showed that the implementation of the Spontaneous Group Discussion method was able to provide an increase in students' speaking skills in class VIII at SMP Muhammadiyah 1 Jember. The calculated t value obtained through the t test is 0.00 <0.05, so Ha is accepted and Ho is rejected at 95% confidence level. Therefore, the hypothesis (Ha) namely "there is a significant effect of the utilization of Spontaneous Group Discussion method on speaking skills in class VIII students of SMP Muhammadiyah 1 Jember" and proven and also statistically accepted.